Evidence of health care offered to women in situations of violence - Laura Ferreira Cortes; Jaqueline Arboit; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula (Rev Rene)
Objective: to analyze the scientific evidence of enhancing and limiting factors of the care rendered to women in situation of violence. Methods: integrative review developed in Latin American and Caribbean Health Sciences database and Public Medline database. The corpus of the research included thirty studies. Results: the factors that enhance attention are related to services organization, conceptions and actions of professionals guided by strategies of communication and identification of violence. The limitating factores are conceptions of professionals grounded in traditional roles of genders, lack of training, protocols for the care and registration of cases, attitudes based on personal style and assistance focused in physical symptoms. Conclusion: the evidence points to the realization of screening and creation of protocols of assistance permeated by listening and guidelines directed to women ensuring the continuity of care network. There is a pressing need for investment in vocational training to provide of visibility to the theme in the health context.